Application of Balanced Fertilizers Reduces the Incidence of Fall Armyworm in Maize Crop - Chiluwal, Kashinath; Timilsina, Sandip; Shrestha, Kailash; Shrestha, Eni; Devkota, Shilpa; Sigdel, Sharad; Shah, Lalit (Journal of the Plant Protection Society, 2024)
Fall armyworm (FAW), a selective polyphagous pest, has become the global limiting factor for maize production. Its damaging parameters; percent infestation, percent damage for maize plant leaves, leaf damage score and maize grain yield were evaluated under a long-term fertility assessment plots at Lumle, Kaski, Nepal in 2020 and 2021. The significantly lowest infestation (41.02% in 2020 and 12.45% in 2021), percent damage (20.04 in 2020 and 18.07 in 2021) and the leaf damage score (1.62 in 2020 and 1.10 in 2021) were recorded in plots receiving balanced fertilizers (NPK @ 120:60:40 kg and 2 t FYM /ha). Ultimately, the maize grain yield (3.04 t/ha in 2020 and 3.72 t/ha in 2021) was also the significantly highest in balanced fertilizer (NPK @ 120:60:40 kg and 20 t FYM/ ha) applied plots followed by the FYM only applied plot (2.18 t/ha in 2020 and 2.644 t/ha in 2021). This study suggests to consider the incorporation of organic sources along with chemical fertilizer to reduce the incidence of FAW in maize crop.